2019
DOI: 10.1111/jace.16643
|View full text |Cite
|
Sign up to set email alerts
|

The effect of grain boundary on the visible light absorption of BaTi1‐x[Ni1/2Nb1/2]xO3‐δ ferroelectric ceramics

Abstract: (Ni2+, Nb5+) co‐doped BaTiO3 ceramics BaTi1‐x(Ni1/2Nb1/2)xO3‐δ (BTNN‐100x) are prepared by a solid‐state reaction method, and their electrical and light absorption properties are investigated. The results show that BTNN‐100x can generate oxygen vacancies which pin the domain walls. BTNN‐100x bulk ceramics show strong visible light absorption. However, the phenomenon of visible light absorption disappear for BTNN‐100x ceramic powders, and the band gap of doped ceramic powders are nearly unchanged. The experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Although having been proven by KN-, KNN-and NBT-based compositions, the effectiveness of the Ni 2+ -oxygen vacancy doping strategy for band gap engineering of perovskite oxides was questioned by a BT-based composition. It was found that by doping 1-4 mol % BNNO into BT, the sintered ceramics showed band gaps of 1.4-1.9 eV with d 33 values of 70-130 pC/N (Lou et al, 2019). However, the powders made by crushing the sintered ceramics showed the same band gap of 3.1 eV which was identical to that of the undoped BT (Lou et al, 2019).…”
Section: Ni-doped Nbt-based and Bt-based Compositions (Nbt-btno And Bmentioning
confidence: 95%
See 4 more Smart Citations
“…Although having been proven by KN-, KNN-and NBT-based compositions, the effectiveness of the Ni 2+ -oxygen vacancy doping strategy for band gap engineering of perovskite oxides was questioned by a BT-based composition. It was found that by doping 1-4 mol % BNNO into BT, the sintered ceramics showed band gaps of 1.4-1.9 eV with d 33 values of 70-130 pC/N (Lou et al, 2019). However, the powders made by crushing the sintered ceramics showed the same band gap of 3.1 eV which was identical to that of the undoped BT (Lou et al, 2019).…”
Section: Ni-doped Nbt-based and Bt-based Compositions (Nbt-btno And Bmentioning
confidence: 95%
“…Figure 1 compares the band gaps and d 33 values of different compositions discovered to date for both wide and narrow gap piezoelectrics. It can be noticed in the figure that, although the currently experimented band gap engineering methodologies are believed to degrade ferroelectricity to some extent (Bai et al, 2018a;Bai et al, 2019a (Bai et al, 2017b;Xiao et al, 2019a;Lou et al, 2019;Zhong et al, 2019). This fact gives the narrow band gap piezoelectrics an obvious advantage over their wide band gap counterparts, i.e., the narrow band gap piezoelectrics can effectively absorb the majority of visible lights while exhibiting an uncompromized piezoelectric response, which can clearly be seen in Figure 1.…”
Section: Narrow Band Gap Piezoelectricsmentioning
confidence: 99%
See 3 more Smart Citations